2021
DOI: 10.1155/2021/8658314
|View full text |Cite
|
Sign up to set email alerts
|

Gymnema inodorum (Lour.) Decne. Extract Alleviates Oxidative Stress and Inflammatory Mediators Produced by RAW264.7 Macrophages

Abstract: Gymnema inodorum (Lour.) Decne. (G. inodorum) is widely used in Northern Thai cuisine as local vegetables and commercial herb tea products. In the present study, G. inodorum extract (GIE) was evaluated for its antioxidant and anti-inflammatory effects in LPS plus IFN-γ-induced RAW264.7 cells. Major compounds in GIE were evaluated using GC-MS and found 16 volatile compounds presenting in the extract. GIE exhibited antioxidant activity by scavenging the intracellular reactive oxygen species (ROS) production and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 59 publications
2
27
0
Order By: Relevance
“…This plant is indigenous in Southeast Asia including Thailand, particularly in the northern part of the country, and is widely consumed [ 6 ]. G. inodorum leaf extract showed high antioxidant and anti-inflammatory activities with polyphenols and flavonoids as the major compounds [ 7 ]. It has also been found that the leaf extract of G. inodorum could decrease blood glucose by inhibiting glucose absorption [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This plant is indigenous in Southeast Asia including Thailand, particularly in the northern part of the country, and is widely consumed [ 6 ]. G. inodorum leaf extract showed high antioxidant and anti-inflammatory activities with polyphenols and flavonoids as the major compounds [ 7 ]. It has also been found that the leaf extract of G. inodorum could decrease blood glucose by inhibiting glucose absorption [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dose of 500 mg/kg GIE was the most effective compared with the doses of 100 and 250 mg/kg. There was a possibility that apart from polyphenols and other compounds in GIE such as flavonoids, alkaloids, triterpenoids, saponins, quercetins, and gymnemic acids, they may have resulted individually or synergistically in the observed antihypoglycemic, antidyslipidemia, hepatoprotective, and nephroprotective activities of GIE treatment in the present study [ 10 , 14 , 45 ]. This extract might stimulate some antioxidant enzymes involved in the fight against oxidative stress, causing less damage to the host.…”
Section: Discussionmentioning
confidence: 99%
“…This extract might stimulate some antioxidant enzymes involved in the fight against oxidative stress, causing less damage to the host. The recent finding showed the antioxidant properties of GIE by regulating the reactive oxygen species production and activating the antioxidant gene, superoxide dismutase 2 expression, which leads to the suppression of proinflammatory cytokines, interleukin 6 (IL-6), and production and downregulation of inflammatory genes such as cyclooxygenase-2, inducible nitric oxide synthase, and IL-6 mRNA levels in murine macrophages [ 14 ]. Consistent with the reports on the pharmacological properties of G. sylvestre , gymnemic acid might play a crucial role in the protective effects through antioxidant and anti-inflammatory activities [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAW264.7 cells were cultured for 12 h in a working solution containing 10% fetal bovine serum, 1% double antibody (100 IU/mL penicillin and 100 IU/mL streptomycin), and 90% Dulbecco’s modified eagle medium (DMEM) in an incubator (Heracell 240i, Waltham, USA) at 37 °C and 5% CO 2 [ 48 ].…”
Section: Methodsmentioning
confidence: 99%